E-Whanaungatanga: The role of social media in Māori political empowerment - Waitoa, Joanne; Scheyvens, Regina; Warren, Te Rina (AlterNative: An International Journal of Indigenous Peoples, 2015)
Lower voter turnout and lack of political empowerment sees Māori engaging less than Pākehā (European New Zealanders) with the political system to the detriment of Māori development. This paper explores the potential of social media to enhance Māori development via political engagement. Mana Party Facebook pages are used as a case study to investigate if social media can encourage Māori political awareness and participation. Results found that social media has both positive and negative implications for political engagement and indigenous development. While social media aligns with tikanga Māori (values/customs) through tino rangatiratanga (self-determination) and whanaungatanga (relationships/networks), other aspects such as cultural misappropriation conflict with Māori values. The paper explores tensions in the use of social media for political engagement among indigenous peoples and offers a framework promoting e-whanaungatanga to illustrate how they might use social media in a way that emphasizes the positive and mitigates the negative aspects of the platform.